2016
DOI: 10.1063/1.4967840
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for light induced degradation in MAPbI3 perovskite thin films and solar cells

Abstract: Organometal halide perovskites are highly promising materials for photovoltaic applications, yet their rapid degradation remains a significant challenge. Here, the light-induced structural degradation mechanism of methylammonium lead iodide (MAPbI3) perovskite films and devices is studied in low humidity environment using X-Ray Diffraction, Ultraviolet-Visible (UV-Vis) absorption spectroscopy, Extended X-ray Absorption Fine Structure spectroscopy, Fourier Transform Infrared spectroscopy, and device measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
209
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(222 citation statements)
references
References 22 publications
12
209
1
Order By: Relevance
“…The combination of reduced grain size throughout the film and a higher defect density serve as the cause for a lower fill factor (FF) and short-circuit current density (J SC ) in sol-eng devices, resulting in a lower overall efficiency. [18,20,48] This observation and our measurements of the local temperature demonstrate that light induced heating effects alone do not result in a degradation of the perovskite film on this timescale and the observed degradation is a consequence of exposure to light and oxygen. [42,45,46] For the PbAc 2 recipe, the inherent water in the precursor solution as well as the addition of hypophosphorous acid results in an enlargement of the grain size and improved film morphology resulting in perovskite films with high electronic quality and low defect density.…”
Section: Photovoltaic Performancesupporting
confidence: 57%
See 1 more Smart Citation
“…The combination of reduced grain size throughout the film and a higher defect density serve as the cause for a lower fill factor (FF) and short-circuit current density (J SC ) in sol-eng devices, resulting in a lower overall efficiency. [18,20,48] This observation and our measurements of the local temperature demonstrate that light induced heating effects alone do not result in a degradation of the perovskite film on this timescale and the observed degradation is a consequence of exposure to light and oxygen. [42,45,46] For the PbAc 2 recipe, the inherent water in the precursor solution as well as the addition of hypophosphorous acid results in an enlargement of the grain size and improved film morphology resulting in perovskite films with high electronic quality and low defect density.…”
Section: Photovoltaic Performancesupporting
confidence: 57%
“…[2] Although the issue of device stability has attracted increased attention of the photovoltaic research community in the last two years, reports that systematically study the fundamental causes (e.g., heat, electrical stress, humidity, oxygen, (UV) light, chemical precursors, processing conditions, influence of film quality and morphology) and mechanisms limiting the material and device stability remain scarce. [16][17][18][19][20] It has been shown that photoexcited electrons in the perovskite layer can form superoxide (O 2 − ) via electron transfer to molecular oxygen, which through deprotonation of the methylammonium cation in turn results in irreversible material degradation. [16][17][18][19][20] It has been shown that photoexcited electrons in the perovskite layer can form superoxide (O 2 − ) via electron transfer to molecular oxygen, which through deprotonation of the methylammonium cation in turn results in irreversible material degradation.…”
mentioning
confidence: 99%
“…In am oisture-free environment, the combination of O 2 and light may also lead to the degradation of CH 3 NH 3 PbI 3 .As per Reactions (8) and (9), CH 3 NH 3 PbI 3 reacts with O 2 to form an O 2 À radical which then reacts with the CH 3 NH 3 + cation to yield CH 3 NH 2 ,P bI 2 ,I 2 ,and H 2 O. [44] CH 3 NH 3 PbI 3 ðsÞþO 2 $ hn CH 3 NH 3 PbI 3 * ðsÞþO 2 * À ð8Þ…”
Section: Resultsmentioning
confidence: 97%
“…[4][5][6][7][8] These approaches include modification of the perovskite structure via halide engineering, [9][10][11][12] cation substitution and the addition of dopants, [13][14][15][16][17] interface engineering, [18][19][20][21][22] and surface passivation [23] or encapsulation via small molecules or waterproof layers. [4][5][6][7][8] These approaches include modification of the perovskite structure via halide engineering, [9][10][11][12] cation substitution and the addition of dopants, [13][14][15][16][17] interface engineering, [18][19][20][21][22] and surface passivation [23] or encapsulation via small molecules or waterproof layers.…”
Section: Introductionmentioning
confidence: 99%
“…Studies focused on colloidal PQDs because of their good optoelectronic properties and high PLQY in nonpolar solvents. Stability of PQDs poses a major problem for practical applications in LEDs.…”
Section: Stability Of Pqdsmentioning
confidence: 99%